Magnesium-L-threonate treats Alzheimer's disease by modulating the microbiota-gut-brain axis - Liao, Wang; Wei, Jiana; Liu, Chongxu; Luo, Haoyu; Ruan, Yuting; Mai, Yingren; Yu, Qun; Cao, Zhiyu; Xu, Jiaxin; Zheng, Dong; Sheng, Zonghai; Zhou, Xianju; et al. (Neural regeneration research, 2024)
Disturbances in the microbiota-gut-brain axis may contribute to the development of Alzheimer's disease. Magnesium-L-threonate has recently been found to have protective effects on learning and memory in aged and Alzheimer's disease model mice. However, the effects of magnesium-L-threonate on the gut microbiota in Alzheimer's disease remain unknown. Previously, we reported that magnesium-L-threonate treatment improved cognition and reduced oxidative stress and inflammation in a double-transgenic line of Alzheimer's disease model mice expressing the amyloid-β precursor protein and mutant human presenilin 1 (APP/PS1). Here, we performed 16S rRNA amplicon sequencing and liquid chromatography-mass spectrometry to analyze changes in the microbiome and serum metabolome following magnesium-L-threonate exposure in a similar mouse model. Magnesium-L-threonate modulated the abundance of three genera in the gut microbiota, decreasing Allobaculum and increasing Bifidobacterium and Turicibacter. We also found that differential metabolites in the magnesium-L-threonate-regulated serum were enriched in various pathways associated with neurodegenerative diseases. The western blotting detection on intestinal tight junction proteins (zona occludens 1, occludin, and claudin-5) showed that magnesium-L-threonate repaired the intestinal barrier dysfunction of APP/PS1 mice. These findings suggest that magnesium-L-threonate may reduce the clinical manifestations of Alzheimer's disease through the microbiota-gut-brain axis in model mice, providing an experimental basis for the clinical treatment of Alzheimer's disease.